Konseling Keluarga Sebagai Alternatif Mediasi Pasca Perceraian - Hidayatullah, Maramis Nur (Al-Mizan (e-Journal), 2025)
Divorce (talaq) is the last way that is allowed to resolve domestic problems that cannot be repaired anymore. However, Islam also advocates reconciliation efforts before talaq is pronounced. Mediation is carried out by judge mediators and non-judge mediators who have participated in the Special Education for the Mediator Profession (PKPM) organized by institutions that have been accredited by the Supreme Court. In carrying out its duties and functions, it must refer to Supreme Court Regulations No. 1 of 2016 concerning Mediation Procedures in Court. This research was carried out at the Religious Court Class 1A Yogyakarta. This study uses a qualitative research method with the aim of analyzing a phenomenon or problem of post-divorce settlement and finding a prototype of an effective family counseling model in post-divorce mediation. In the context of post-divorce mediation, family counseling aims to: (1) help family members understand and overcome complex emotions such as sadness, anger, and disappointment; (2) facilitate open and honest communication between ex-spouses and children, (3) help family members develop effective coping skills to cope with change, and 4) create a parenting plan that is best for the child's well-being. Some commonly applied family counseling models in post-divorce mediation include: (1) structural model; (2) strategic model; and (3) focus emotive model. Family counseling is a complex process and requires special expertise, for this reason, post-divorce family counseling should be carried out by a professional counselor so that what is a post-divorce problem can be resolved properly, and the parties can establish a good relationship even though they have been divorced.